PENINDAKAN PELANGGARAN PEMILIHAN UMUM OLEH BADAN PENGAWAS PEMILU KOTA SAMARINDA - Dinny Wirawan Pratiwie; Tumbur Ompu Sunggu; Gabriel Satw Satw (Law Department, University of Widya Gama Mahakam Samarinda, 2024)
Based on the Constitution of the Republic of Indonesia, the implementation of general elections is a reflection of the application of the concept of democracy which is emphasized in Article 1 paragraph (2) which reads